Strategi Pengelolaan Pendapatan dalam Mengoptimalkan Operasional Perguruan Tinggi Swasta - Prima, Anggra; Rachim, Abd.; Satriah, Satriah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
Effective financial management is vital for private universities in ensuring operational sustainability and improving the quality of education. However, many private universities, especially those located in areas far from large cities, face major challenges in managing their sources of income. Based on previous research, there is still a gap in understanding in depth how to calculate and manage sources of income in private universities, especially in the local context. This study aims to identify and analyse sources of income, mechanisms for managing and calculating income, and challenges faced by STAI Sangatta East Kutai in optimising income. The research method used is a case study with a qualitative approach, through interviews and document analysis. The main findings of this study indicate that financial management at STAI Sangatta East Kutai shows significant challenges, especially related to sudden needs that are not planned in the Budget and Cost Plan and initial budget limitations. To overcome these obstacles, STAIS has implemented various innovative solutions, such as optimising temporary funds, returning the budget after the next disbursement, and prioritising programs with spending efficiency. In addition, strategic steps such as strengthening relations with local governments, increasing the efficiency of fund management, and developing independent income strategies through flagship programs have contributed to the sustainability of the institution's operations. This adaptive and strategic approach not only strengthens the financial stability of STAI Sangatta East Kutai but also becomes a relevant management model for similar institutions facing higher education financing dynamics.